Finite element modelling of abdominal aortic aneurysm - Mohd Izzat, Samsudin (2010)
An aneurysm is an abnormal bulging or widening of a portion of an artery due to weakness in the wall of the aortic wall. This is happening when the mechanical stress exceeds the tensile strength of the tissue. Aneurysm can happens anywhere in parts of our body as long there is an aorta. Nowadays, an accurate decision to predict the rupture of the aneurysm is not is founded yet and usually, clinical doctors will treat the aneurysm base on the aneurysm size. This study is focusing on abdominal aortic aneurysm that is occurring at the area of abdomen aorta. By using the simulation tools, the stress behavior on this region will be analyzed. The normal size of abdomen aorta is about 2 cm and aneurysm can make this aorta to reach to 6 cm. As the size of an aneurysm increases, there is a potential of rupture of aneurysm. This can result in severe hemorrhage or even worst, fatal event. The studies being proceed without experiment but only based on numerical approach. From the previous studies, it was shown that the mechanical behaviors inside aneurysm region would be different compare to the normal blood vessel. The effective wall stress showed large variations on the size and form of aneurysm. It was proves that a large stress distribution appear at both necks and around the aneurysm bulge on the anterior surfaces. Studying the mechanical properties in real AAAs would be useful information to the clinical doctors because it helps them to better understand of aneurysm behavior.